PENGARUH BUDAYA ORGANISASI DAN PENGEMBANGAN KARIER TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN - FX. Suwarto (Jurnal Manajemen., 2015)
This research was conducted to study and examine the influence of organizational culture and career development, job satisfaction and its impact on the performance of employees so as to know this, the researchers analyzed the data and test hypotheses specifically about the effect of work culture and career development to the level of employee satisfaction and its impact on employee performance. The object of research is done in service companies ritail Department Store in Kab.Klaten. To be able to accommodate all of the above terbut researchers used a descriptive analytical type of research, in order to test hypotheses with survey research methods, while the sampling technique by applying probability sampling, Sedankan for data analysis using path analysis/path analysis. The results showed that the work culture and careerdevelopment patterns affect the level of job satisfaction, further work culture and career development patterns also affect the performance of employees, as well as employee satisfaction influence on employee performance. Specifications output/outcome specifikation results of this study are expected to be entered for entrepreneurs ritail services department store in the district. Klaten with the expectations of the leadership of the department store in the area Kab.Klaten can formulate a human resource development strategy right/in accordance with the development of business in generating program development and quality of human resources which have high value. Besides, this research also can provide useful information to management/offender retail services, as well as an input in optimizing the performance of employees. Implications If the employer/principal retail services are not prioritized in developing, managing and developing human resources more targeted/programmed, the development of human resources in the organization can not have competitif advanted line with developments in the business world department store retail services business. Development and sustainability of the business services department store retail area of Klaten city can eventually contribute increasing revenue in Klaten district.